Sweet sorghum juice as an alternative carbon source and adaptive evolution of Lactobacillus brevis NIE9.3.3 in sweet sorghum juice and biodiesel derived crude glycerol to improve 1, 3 propanediol production - Alphy, Maria Paul; Anjali, Kodakkattil Babu; Vivek, Narisetty; Thirumalesh, Banjagere Veerabhadrappa; Sindhu, Raveendran; Pugazhendi, Arivalagan; Pandey, Ashok; Binod, Parameswaran (Elsevier, 2021)
Sweet sorghum juice (SSJ) is considered as an ideal complement for carbon supplement in ethanol fermentation for its ease of cultivation. Extraction of fermentable sugars from the sweet sorghum is very simple in comparison to lignocellulosic biomass. Hence sweet sorghum is a suitable candidate as a feedstock. In the present study, batch fermentations were carried out using Lactobacillus brevis NIE9.3.3, a facultative anaerobe, isolated through onsite enrichment technique to produce 1,3-propanediol and other co-metabolites, in glucose-glycerol co-fermentation. To make the process more sustainable, the glucose supplemented in the production media was replaced with SSJ. The supplementation of 40 g/L sorghum juice and 40 g/L crude glycerol in the production media resulted in the titre of 25.9 g/L 1, 3-PDO with a volumetric yield of 0.64 g 1,3-PDO/g glycerol. Adaptation of the microorganisms and cultivation under controlled conditions of temperature and substrate concentrations followed by selection was carried out, that is, adaptive evolution. Among the adaptively evolved strains, PD 20.100 has displayed better performance and increased the titres up to 38.4 g/L with a volumetric yield of 0.64 g 1,3-PDO/g glycerol. The industrial applicability of the fermentation process was checked in pilot scale and the production yield was comparable with that of flask scale. The utilization of agricultural and biodiesel industrial waste for the production of 1,3-PDO by a non-pathogenic organism and the strain improvement through ALE for better utilization and conversion of substrates indicates the novelty of this work.
Keywords: Sweet sorghum juice; 3-PDO; Adaptive evolution; Lactobacillus brevis NIE9.3.3; Co-fermentation